Endocrinopathies in Inborn Errors of Immunity - Takasawa, Kei; Kanegane, Hirokazu; Kashimada, Kenichi; Morio, Tomohiro (Frontiers in Immunology, 2021)
Inborn errors of immunity (IEI), caused by hereditary or genetic defects, are a group of more than 400 disorders, in which the immune system, including lymphocytes, neutrophils, macrophages, and complements, does not function properly. The endocrine system is frequently affected by IEI as an associated clinical feature. The endocrine system is a complex network of glands which regulate many important body functions, including growth, reproduction, homeostasis, and energy regulation. Most endocrine disorders associated with IEI are hypofunction which would be treated with supplementation therapy, and early diagnosis and appropriate management are essential for favorable long-term outcomes in patients with IEI. In this review, we aimed to comprehensively summarize and discuss the current understanding on the clinical features and the pathophysiology of endocrine disorders in IEI. This review is composed with three parts. First, we discuss the two major pathophysiology of endocrinopathy in IEI, autoimmune response and direct effects of the responsible genes. Next, the details of each endocrinopathy, such as short stature, hypothyroidism, hypoparathyroidism, adrenal insufficiency, diabetes mellitus (DM) are specified. We also illustrated potential endocrinopathy due to hematopoietic stem cell transplantation, including hypogonadism and adrenal insufficiency due to glucocorticoid therapy.